Utrecht law review (Igitur, Universiteit Utrecht, 2005)
Utrecht Law Review offers an international platform for cross-border legal research. It aims to publish articles by both Dutch and foreign authors concerning legal issues in general in its regular issues and, in its annual special issue, concerning legal issues centred on a particular theme.